Impact of the Neuro-Radiologist and Neuro-Surgeon in Contouring With the Neuro-Oncologist on Local Relapse Rates for Brain Metastases Treated With Stereotactic Radiosurgery. (1st October 2022) - Robinson, Maxwell; Sayal, Karen; Tunstall, Clare; Padmanaban, Sriram; Watson, Rhona; Pretorious, Pieter; Joseph, Robin; Jeyaretna, Sanjeeva; Hobbs, Claire
Abstract: AIMS: The audit evaluates the value of MDT, including neuro-radiologist and neuro-surgeon, review of contouring carried out by a clinical oncologist in stereotactic radiosurgery (SRS). METHOD: Lesions were contoured first by clinical oncologist then reviewed/edited by MDT. Iinitial contour was compared with final using Jaccard conformity and geographical miss indices. Dosimetric impact of contouring change was assessed using plan metrics to both original and final contour. The impact of contouring review on local relapse, overall survival and radio necrosis rate was evaluated with at least 24 months follow up. RESULTS: 113 patients and 142 lesions treated over 22 months were identified. Mean JCI was 0.92 (0.32-1.00) and 38% needed significant editing (JCI<0.95). Mean GMI was 0.03 (0.0-0.65) and 17% showed significant miss (GMI>0.05). Resection cavities showed more changes, with lower JCI and higher GMI (p<0.05). Dosimetric analysis indicated a strong association of conformity with PTV dose metrics. Greater association was seen in resection cavity, i.e. geographical nature of a typical contouring error gives rise to greater potential change in dose. Clinical outcomes compared well with published series. Median survival was 20 months and local relapse free rate of 0.89 (0.8-0.94) at 40 months. Radio-necrosis free rate 0.9 (0.83-0.95) at 40 months with median 17 months to developing radionecrosis for those that did. CONCLUSION: MDT contour review adds significant value to SRS resulting in reduced local recurrence rates. No improvement in clinical oncologist contouring over time was shown indicating a collaborative approach is needed regardless of experience of clinical oncologist - particularly for resection cavities.